Medindo um envolvimento paterno multidimensional: validação brasileira do inventory of father involvement - Santis, Ligia de (2016)
Research indicates that the involvement of fathers in raising their children results in benefits for their children’s development, their marital relationships and their sense of competence as fathers. However, it is difficult to evaluate intervention programs that aim to strengthen interactions between fathers and their children, in Brazil, as there is not a model of father involvement based on the integration of results of empirical studies, and there are no validated instruments available to measure father involvement. As such, the objectives of this study were to: (a) review and integrate the results of empirical studies of father involvement (Study 1), and (b) continue efforts to validate the Inventory of Father Involvement (IFI), already translated and adapted for use in Brazil (IFI-BR) (Study 2). In Study 1, 39 full texts that included data on father involvement were retrieved via a systematic search of databases (APA PsycNET, Bireme, PEPSIC, Web of Science (using the periódicos CAPES gateway) and IndexPsi Periódicos) using the keywords “involvement” and “father”, crossed with “measure”, “scale”, “tool” or “instrument”, in both the English and Portuguese languages. The model presented synthesizes the results of these studies, representing an advance in theory development in this area by integrating factors that influence father involvement and outcomes for the different people involved in this context. In Study 2, participants included 200 fathers of children between 5 to 10 years of age, residing in two cities in the interior of the State of São Paulo, Brazil. The fathers were 39.5 years old (sd = 7.42), on average; 91% reported being married or cohabiting; 46.7% stated that they had completed an undergraduate university degree, and 35.9% had either completed high school or had not yet completed their undergraduate studies.The instruments used in this study included: the IFI-BR; the Social Skills Rating System-BR, or the Inventário Portage Operacionalizado (modified), depending on the age of the child; the Marital Satisfaction Questionnaire; a Stress Scale; scales to evaluate difficulties in the quality of the father-child relationship; and the Critério de Classificação Econômica Brasil. For eight of the nine factors of the IFI, the reliability of the IFI-BR varied between .652 and .815. These factors were: a) discipline and teaching responsibility, b) school encouragement, c) mother support, d) providing, e) time and talking together, f) praise and affection, g) reading and homework support, and h) attentiveness. On the basis of a confirmatory factor analysis, in addition to high factor loadings, the final model presented satisfactory indicators of adjustment to the structure of the IFI. With respect to evidence for external validity, correlations varied between .229 and .550 between scores on the IFI-BR and the other measures, confirming relationships observed in previous studies and that are included in the theoretical model of father involvement, presented at the end of Study 1. In future studies, if further evidence for the validity of the Brazilian version of this instrumentcan be obtained, it will be a useful tool for the evaluation of intervention programs that aim to increase father involvement.